Production of peptides as generic drugs: a patent landscape of octreotide. (2nd April 2016) - Sabatino, Giuseppina; Guryanov, Ivan; Rombecchi, Andrea; Zanon, Jacopo; Ricci, Antonio; Cabri, Walter; Papini, Anna Maria; Rovero, Paolo
ABSTRACT: Introduction : New low-cost strategies and enhancement of the already described methods to manufacture peptide molecules on an industrial scale are highly requested, particularly for peptides such as octreotide, which, along with goserelin and leuprolide, dominate the global peptide market. A number of patents related to the production of octreotide can be found, concerning both solution and solid-phase synthesis. Thus, there is a need to revise the existing synthetic approaches in order to organize them in a more comprehensible way. Area covered : The octreotide patent landscape could help improvement of the methods for manufacturing of octreotide in industrial scale, leading to the appearance of innovative approaches. Expert opinion : The pharmaceutical value of octreotide can be seen from its high market percentage among other peptide drugs. The complex chemical structure of octreotide represents the main challenge for its industrial production. Two synthetic steps are crucial in the preparation of octreotide: (i) threoninol attachment or on resin formation working in solid-phase and (ii) disulphide bond formation to achieve cyclic structure. Analysis of various patents filed to date allows us to see the trend in simplification of the synthetic approaches from the labor intensive syntheses in solution to the more versatile and rapid solid-phase methods.